The Son as a Torn Veil: The Mysteries of Jesus According to J. Ratzinger-Benedict XVI - Szymik, Jerzy (Collectanea Theologica, 2021)
J. Ratzinger-Benedict XVI relates theological cognition to following Jesus and going in His footsteps. He emphasizes the inseparable, mutual, servant-like relationship between academic theology and Christian praxis, Christological hermeneutics with the existential basis of faith. Intellectual and spiritual understanding of the mystery of Jesus depends on intimacy with Him and grows on this path: only the Son can show the Father because he knows Him in a way that defines his existence as the Son. The eternal inter-Trinitarian conversation with the Father – the prayer of the Son, His sonship-obedience – finds its corporal expression in history, and the humanity of Jesus, whose culmination is the cross, remains His prayer. The earthly life, and finally the Passover of Jesus, introduces into the human, vague concept of God the experience of the loving Father, thus making the course of history definitively meaningful and fulfilling, and the faith legitimate. Ratzinger defends Christology as a conceptual understanding of the truth of the Gospel, the depth and integrity of which Christology guards and to which it refers. Disregarding in faith the cognitive achievements and heritage of systematic theology leads to depriving faith of its most important contents, without which it starts to look in the dark for justifications which are subjective as well as fuzzy.